Effects of live Brucella abortus strain 19 vaccine on reindeer later challenge exposed with Brucella suis type 4 - Robert A. Dieterich; Jamie K. Morton (Rangifer, 1987)
Twelve reindeer (Rangifer tarandus) were vaccinated with Brucella abortus strain 19 vaccine and challenge exposed with B. suis type 4 two and one-half months later during mid-gestation. An additional 10 reindeer served as non-vaccinated controls. A sharp serologic titer response was observed in both vaccinates and controls. Brucella suis type 4 was isolated from tissues and blood from most controls (8 of 10, and 7 of 10 respectively). Seven of 11 vaccinated cows aborted, gave birth to weak fawns that died, or were not pregnant at the completion of the experiment. Brucella suis type 4 was isolated from the tissue of 4 of 12 vaccinates at necropsy. It was concluded that, under the conditions of this experiment, B. abortus strain 19 vaccine in reindeer did not provide adequate protection against challenge exposure with virulent B. suis type 4 organisms.